Carcinoma-associated fibroblast-derived lysyl oxidase-rich extracellular vesicles mediate collagen crosslinking and promote epithelial-mesenchymal transition via p-FAK/p-paxillin/YAP signaling - Xue Liu; Jiao Li; Xuesong Yang; Xiaojie Li; Jing Kong; Dongyuan Qi; Fuyin Zhang; Bo Sun; Yuehua Liu; Tingjiao Liu (International Journal of Oral Science, 2023)
Abstract Carcinoma-associated fibroblasts (CAFs) are the main cellular components of the tumor microenvironment and promote cancer progression by modifying the extracellular matrix (ECM). The tumor-associated ECM is characterized by collagen crosslinking catalyzed by lysyl oxidase (LOX). Small extracellular vesicles (sEVs) mediate cell-cell communication. However, the interactions between sEVs and the ECM remain unclear. Here, we demonstrated that sEVs released from oral squamous cell carcinoma (OSCC)-derived CAFs induce collagen crosslinking, thereby promoting epithelial-mesenchymal transition (EMT). CAF sEVs preferably bound to the ECM rather than being taken up by fibroblasts and induced collagen crosslinking, and a LOX inhibitor or blocking antibody suppressed this effect. Active LOX (αLOX), but not the LOX precursor, was enriched in CAF sEVs and interacted with periostin, fibronectin, and bone morphogenetic protein-1 on the surface of sEVs. CAF sEV-associated integrin α2β1 mediated the binding of CAF sEVs to collagen I, and blocking integrin α2β1 inhibited collagen crosslinking by interfering with CAF sEV binding to collagen I. CAF sEV-induced collagen crosslinking promoted the EMT of OSCC through FAK/paxillin/YAP pathway. Taken together, these findings reveal a novel role of CAF sEVs in tumor ECM remodeling, suggesting a critical mechanism for CAF-induced EMT of cancer cells.